2014
DOI: 10.1371/journal.pone.0105710
|View full text |Cite
|
Sign up to set email alerts
|

Chemo-Predictive Assay for Targeting Cancer Stem-Like Cells in Patients Affected by Brain Tumors

Abstract: Administration of ineffective anticancer therapy is associated with unnecessary toxicity and development of resistant clones. Cancer stem-like cells (CSLCs) resist chemotherapy, thereby causing relapse of the disease. Thus, development of a test that identifies the most effective chemotherapy management offers great promise for individualized anticancer treatments. We have developed an ex vivo chemotherapy sensitivity assay (ChemoID), which measures the sensitivity of CSLCs as well as the bulk of tumor cells t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 43 publications
0
42
0
Order By: Relevance
“…Our recent clinical studies showed that patient derived CSCs from primary cancer cell cultures can be used in a drug response assay. 9,[30][31][32][33][34][35][36] We have optimized the enrichment of CSCs from tumor biopsies and have developed the ChemoID Âź chemotherapy response assay, which measures the sensitivity of CSCs and bulk of tumor cells to chemotherapy to determine the most effective combination of anticancer drugs for solid tumors. 9,[30][31][32][33][34][35][36] …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our recent clinical studies showed that patient derived CSCs from primary cancer cell cultures can be used in a drug response assay. 9,[30][31][32][33][34][35][36] We have optimized the enrichment of CSCs from tumor biopsies and have developed the ChemoID Âź chemotherapy response assay, which measures the sensitivity of CSCs and bulk of tumor cells to chemotherapy to determine the most effective combination of anticancer drugs for solid tumors. 9,[30][31][32][33][34][35][36] …”
Section: Discussionmentioning
confidence: 99%
“…9,[30][31][32][33][34]36 In brief, primary cultures were initiated by spinning down the malignant cells present in the ascites aspirate and by culturing the cells to sub confluence in RPMI-1640 medium supplemented with 5% irradiated, heat inactivated, defined fetal bovine serum (Thermofisher/Hyclone), and 50 U of penicillin and 5 ”g of streptomycin/mL of medium (Thermofisher/Mediatech). Proliferation of CSCs was obtained using a culture methodology previously described 9,31 in which culture media, oxygenation, rotational speed of the culture vessel, temperature and CO2 were kept consistently constant for seven days. Cells were then removed and counted using trypan blue exclusion to determine cellular viability and cell number.…”
Section: Drug Sensitivity Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…However, until now, this approach has been hampered by the chemotherapy testing only being performed on bulk of tumor cells derived from cancer biopsies [8][9][10][11][12][13][14][15][16][17]. GBMs contain a heterogeneous population of cells, among which is a population of self-renewing cancer stem cells (CSCs) that contribute to tumorigenesis, treatment resistance, and tumor recurrence [3,6].…”
Section: Introductionmentioning
confidence: 99%